THE ECONOMIC IMPACT OF SMOKING AMONG INDONESIAN POPULATION: PREMATURE MORTALITY COSTS AND YEARS OF POTENTIAL LIFE LOST (YPLL) STUDY - Kristina SA1*, Endarti D1, Prabandari YS2, Ahsan A3, Thavorncharoensap M4 (MTCC, John Hopkins n The Union, 2015)
Background: As smoking is the leading preventable cause of multiple diseases and premature death, estimating the burden of disease attributable to smoking has become the standard in documenting the impact of the tobacco epidemic across the world. In Indonesia, there is a dearth of studies assessing the economic costs of smoking. This study aimed to estimate indirect mortality costs of premature deaths and years of potential life lost attributable to smoking among the Indonesian population. Methods: A prevalence based method was employed. Using national data, we estimated smoking-attributable mortality in 2013. Premature mortality costs and years of potential life lost (YPLL) were estimated by calculating number of deaths, life expectancy, annual income, and workforce participation rate. Human capital approach was used to calculate the present value of lifetime earnings (PVLE). Discount rate of 3% was applied. Results: The study estimated that smoking attributable mortality was 156,079 (7.23% of all deaths), comprised of 95% death in men and 5% in women. Smoking was responsible for 2.6 million years of potential life lost. Premature mortality costs caused by smoking accounted for IDR 31 trillion (USD 2.7 billion) in 2013. Conclusions: Smoking brings an enormous economic burden to Indonesia. Therefore, tobacco control efforts need to be prioritized in order to prevent more losses to the nation. The data of this study is important for advocating national tobacco control policy. Keywords: smoking, YPLL, premature mortality cost, Indonesia